INTEGRASI HUKUM ADAT DAN HUKUM NASIONAL DALAM PENYELESAIAN SENGKETA TANAH WARISAN: STUDI KASUS TIGA MARGA DI KECAMATAN LEWA, KABUPATEN SUMBA TIMUR - Maran, Mary Grace Megumi; Peter Lay, Benediktus; Reinaldo Yazakur, Patrick Aleksandro; Sogen, Castyelo Yohanes A; Pramana, Hanif Al Faiq (Gapenas Publisher, 2025)
The purpose of this study is to comprehensively describe and analyze the regulation of land ownership from both national law and customary law perspectives in the context of land inheritance in Lewa District, East Sumba Regency. The research method employed is a normative-empirical legal approach based on library studies. The normative approach involves the review of primary legal sources such as the Basic Agrarian Law and related regulations, while the empirical approach examines secondary data sourced from scientific literature, accredited national journals, customary law documents, mediation archives, and documented local news. Data collection was conducted indirectly through systematic documentation studies and literature reviews, without direct field observation. Data analysis was carried out qualitatively using a descriptive-analytical approach. The analysis process included data reduction by selecting relevant information regarding land ownership regulations according to national and customary law, presentation of data in a systematic thematic narrative, and in-depth analysis linking legal theory, customary norms, and conflict resolution practices as reflected in mediation documents and news sources. Conclusions were drawn based on a comprehensive interpretation of the analyzed data to address the research problems thoroughly. The results indicate that customary law still plays a significant role in resolving inheritance land disputes in East Sumba by emphasizing kinship values and consensus deliberation. However, national law is also important as a final recourse when customary resolution fails. The ideal integration is a synergy between customary and national law with official recognition of customary decisions and national legal protection, enabling land disputes to be resolved fairly and sustainably.